I love spelling! [ - DK Interactive Learning (Firm) (New York : Dorling Kindersley, 2005)
These animated adventure games feature 6 spelling games, 5,000 spelling words graded into 3 levels, and 50 spelling-pattern word groups that target problem areas. Games contain more than 100 themed word groups, test spelling, and automatically recycle misspelled words
Title from disc label
Ages 7-11
System requirements for Macintosh: 68LC040/25MHz processor; 8MB RAM (12MB for System 8.0 or higher); System 7.0 or higher; double-speed CD-ROM drive; 14MB available space on hard drive; 256 color screen display, 640 x 480 pixel screen display; 8-bit audio card; loudspeakers or headphones; mouse
System requirements for Windows: 486DX/33MHz PC; 8MB RAM (Windows 95 and Windows 98); Windows 3.1x/95/98; double-speed CD-ROM drive; 5MB available space on hard drive; 256 color screen display, 640 x 480 pixel screen display; 8-bit sound card; loudspeakers or headphone; mouse
Keywords: English language -- Orthography and spelling -- Study and teaching -- Juvenile software